A Behavioral Study of Promethazine Interaction with Analgesic Effect of Diclofenac: Pain Combination Therapy - Niloofar Amidi; Zohreh Izadidastenaei; Malihe Araghchian; Davoud Ahmadimoghaddam (Korean Pharmacopuncture Institute, 2020)
Pain is considered as a cause of sickness and the most prevalent symptom which makes people visit a physician. Nowadays, combination therapy is becoming useful to relieve chronic and postsurgical pain. The aim of this study was to study the promethazine (as an antihistamine) interactions with antinociceptive effect of diclofenac (as a non-steroidal anti-inflammatory drugs). In initial part of the study, we investigate the analgesic effect of diclofenac. Using writhing test, we demonstrate that diclofenac significantly reduces writhe response induced by acetic acid in a dose-dependent manner. In this study, we evaluate the combination effect of promethazine on diclofenac analgesic effect. We observed that diclofenac inhibited pain in the dose dependent manner which means that by increasing dose of diclofenac a significant decrease in pain was observed. This experimental setup allowed calculation of the dose that caused 50% antinociception (ED50) for diclofenac. The ED50 for diclofenac in this study was determined to be 9.1 mg/kg according our previous study. Additionally, promethazine was showed a dose-dependent inhibition of writhes. The combination of different doses of promethazine (2, 4, 6 mg / kg) with diclofenac ED50 (9.1 mg / kg) was injected to mice. Promethazine 4 and 6 mg / kg in combination with diclofenac had significantly led to increase analgesic effect of diclofenac. In conclusion, these results add important information to the existing knowledge on combination of diclofenac and antihistamine in pain therapies to be used in clinical practice and maybe helpful in designing the future guidelines.